2020
DOI: 10.1557/jmr.2020.88
|View full text |Cite
|
Sign up to set email alerts
|

Waterproof and breathable polyacrylonitrile/(polyurethane/fluorinated-silica) composite nanofiber membrane via side-by-side electrospinning

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Differences in composition of FLG in PMMA solutions result in different properties of the mixing solution that was used as precursor solution. Moreover, the interlacing of nonwoven composited NFs can enhance the waterproofing and hydrophobic properties [23], which are factors of importance for corrosion inhibitor materials. The Raman spectroscopy is a typical instrument [24] which was used to assess the electronic and vibrational characteristics of carbon-based materials.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in composition of FLG in PMMA solutions result in different properties of the mixing solution that was used as precursor solution. Moreover, the interlacing of nonwoven composited NFs can enhance the waterproofing and hydrophobic properties [23], which are factors of importance for corrosion inhibitor materials. The Raman spectroscopy is a typical instrument [24] which was used to assess the electronic and vibrational characteristics of carbon-based materials.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Yu et al reported a fibrous membrane based on PU, PAN, and fluor silane-modified silica nanoparticles (F-SiO 2 ). [137] The hydrophobic inorganic F-SiO 2 can improve the roughness and reduce the surface energy of the membrane, consequently improving the hydrophobicity of the nanofibrous membrane. The prepared hybrid porous membranes possess a robust tensile strength of 19.5 MPa, WVT of 10 300 g m −2 d −1 , and a moderate WCA of 137.2°.…”
Section: Modifying Hydrophilicity/hydrophobicitymentioning
confidence: 99%
“…However, in the case of soybean oil and petroleum ether, poor oleophobicity was observed due to the oleophilic nature of PDMS. Researchers developed hydrophobic microporous NF membrane via fluorosilane-modified silica (F-SiO 2 ) nanoparticles, polyurethane and polyacrylonitrile solution [ 157 ]. The presence of flurosilane led to the hydrophobic behavior in the membrane.…”
Section: Electrospun Nf Implantsmentioning
confidence: 99%